Controlled trial of decision support for men with early-stage prostate cancer: brief research report of effects on patient knowledge - Belkora, Jeffrey K.; Broering, Jeanette M.; Neuhaus, John; Zargham, Ali; Weinberg, Tia; Witte, John S.; Kenfield, Stacey A.; Van Blarigan, Erin L.; Cooperberg, Matthew R.; Carroll, Peter R.; Chan, June M. (Frontiers in Urology, 2023)
Introduction: A single-arm pre-post pilot academic setting study found that pre-consultation decision support improved patient knowledge among men with early-stage prostate cancer. We now report on exploratory analyses from a controlled study featuring patients from academic and community settings. Methods: We enrolled 58 men to usual care and 61 men to the intervention. We evaluated whether the intervention was associated with patients answering key knowledge items correctly just before their urology visit. Results: Just prior to the visit, 39/56 (70%) in the intervention group replied correctly to knowledge items, compared to 31/55 (56%) in usual care (p=0.15). At baseline, the intervention group started with 42/60 (70%) correct and the usual care group started with 28/56 (50%) (p=0.03). This imbalance at baseline created a ceiling effect: more men in the usual care group had room to improve on their knowledge scores. Indeed, seven men moved from incorrect to correct in the usual care group, versus 5 in the intervention group; and five men in the intervention group moved from correct to incorrect versus 3 in the usual care group (p=0.44). Discussion: In addition to small sample size, reasons for the null findings may include clustering of highly educated participants at the academic site combined with over-representation of academic site participants in the intervention group. We confirmed, from the pilot study, the feasibility of using pre-health student interns as health coaches. Future research should explore whether increasing adoption of telehealth will improve the feasibility of delivering pre-visit decision support in community settings.